2013
DOI: 10.1089/ars.2012.4625
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Transport: A New Role for PfCRT in Chloroquine Resistance

Abstract: Aims: Chloroquine (CQ) kills Plasmodium falciparum by binding heme, preventing its detoxification to hemozoin in the digestive vacuole (DV) of the parasite. CQ resistance (CQR) is associated with mutations in the DV membrane protein P. falciparum chloroquine resistance transporter (PfCRT), mediating the leakage of CQ from the DV. However, additional factors are thought to contribute to the resistance phenotype. This study tested the hypothesis that there is a link between glutathione (GSH) and CQR. Results: Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 52 publications
2
48
1
Order By: Relevance
“…Given that these changes have been associated with impaired fitness in mutant PfCRT parasites expressing the CQ resistance-conferring Dd2 or 7G8 haplotypes [41], our results raise an obvious question: does Cam734 PfCRT impart a metabolic compensatory mechanism that allows these parasites to circumvent the normally deleterious effects of altered Hb digestion? Previous heterologous expression studies using Xenopus laevis oocytes have suggested that mutant PfCRT isoforms might selectively confer transport of the tripeptide glutathione [57], which was earlier proposed to facilitate the degradation of reactive heme and reduce heme-mediated toxicity [36,83]. However, we saw no significant differences in glutathione or any other redox-associated metabolites (see S4 Fig and S6 Table) between isogenic lines encoding Cam734 or Dd2 PfCRT, suggesting that major redox-related metabolic changes are unlikely to account for the improved fitness associated with the Cam734 pfcrt allele.…”
Section: Discussionmentioning
confidence: 99%
“…Given that these changes have been associated with impaired fitness in mutant PfCRT parasites expressing the CQ resistance-conferring Dd2 or 7G8 haplotypes [41], our results raise an obvious question: does Cam734 PfCRT impart a metabolic compensatory mechanism that allows these parasites to circumvent the normally deleterious effects of altered Hb digestion? Previous heterologous expression studies using Xenopus laevis oocytes have suggested that mutant PfCRT isoforms might selectively confer transport of the tripeptide glutathione [57], which was earlier proposed to facilitate the degradation of reactive heme and reduce heme-mediated toxicity [36,83]. However, we saw no significant differences in glutathione or any other redox-associated metabolites (see S4 Fig and S6 Table) between isogenic lines encoding Cam734 or Dd2 PfCRT, suggesting that major redox-related metabolic changes are unlikely to account for the improved fitness associated with the Cam734 pfcrt allele.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of chloroquine-resistant PfCRT protein levels to approximately 65% of the wild-type levels lessened parasite resistance to chloroquine and led to an alkalinization of the DV (30), suggesting a possible role for CRT in acidification of this compartment. Plant chloroquine-like transporters function in transporting glutathione, and a recent study implicates chloroquine-resistant PfCRT (but not chloroquine-sensitive PfCRT) in glutathione transport into the DV (10,44).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that TgCRT, like plant chloroquine-like transporters and chloroquine resistance alleles of PfCRT (10,44), has a role in transporting glutathione. Dysregulation of glutathione functions in the VAC may then lead to the swelling of this organelle.…”
Section: Discussionmentioning
confidence: 99%
“…GSH has been implicated in modulating antimalarial sensitivity (17,(26)(27)(28). In order to evaluate this notion, the ␥-gcs-disrupted Pb-GFP (⌬gcs) strain was constructed by integrating linearized pL0017-⌬gcs (Fig.…”
Section: Resultsmentioning
confidence: 99%